2019
DOI: 10.1016/j.jamda.2019.03.009
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the FIT-HIP Intervention for Fear of Falling After Hip Fracture: A Cluster-Randomized Controlled Trial in Geriatric Rehabilitation

Abstract: Objectives: Fear of falling (FoF) is common after hip fracture and can impede functional recovery because of activity restriction. The Fear of falling InTervention in HIP fracture geriatric rehabilitation (FIT-HIP intervention) was designed to target FoF and consequently to improve mobility. The aim of this study was to evaluate the effect of the FIT-HIP intervention in patients with FoF in geriatric rehabilitation (GR) after hip fracture. Design, setting, and participants: This cluster-randomized controlled t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 44 publications
(40 reference statements)
0
11
0
Order By: Relevance
“…All participants had FoF, which may have biased the findings regarding symptoms of anxiety and depression. On the other hand, FoF has been reported in as much as 60% of the older patients with hip fracture (Visschedijk et al, 2013), and the level of anxiety reported in the study population was low (Scheffers-Barnhoorn et al, 2019). Also, FoF is not limited to patients with hip fracture; prevalence rates in the general geriatric population and in other geriatric rehabilitation patients are high too (Scheffer, Schuurmans, van Dijk, van der Hooft, & de Rooij, 2008;Visschedijk, Caljouw, Bakkers, van Balen, & Achterberg, 2015).…”
Section: Limitations Of the Present Studymentioning
confidence: 68%
“…All participants had FoF, which may have biased the findings regarding symptoms of anxiety and depression. On the other hand, FoF has been reported in as much as 60% of the older patients with hip fracture (Visschedijk et al, 2013), and the level of anxiety reported in the study population was low (Scheffers-Barnhoorn et al, 2019). Also, FoF is not limited to patients with hip fracture; prevalence rates in the general geriatric population and in other geriatric rehabilitation patients are high too (Scheffer, Schuurmans, van Dijk, van der Hooft, & de Rooij, 2008;Visschedijk, Caljouw, Bakkers, van Balen, & Achterberg, 2015).…”
Section: Limitations Of the Present Studymentioning
confidence: 68%
“…Scheffers-Barnhoorn et al 236 conducted a cluster RCT in inpatient rehabilitation units in the Netherlands to assess the impact of a multicomponent cognitive behavioral intervention, integrated by physical therapists into treatment after surgery for hip fracture, on falls self-efficacy. No differences were found between groups in physical performance, falls efficacy, or self-reported activity restriction.…”
Section: IIImentioning
confidence: 99%
“…Patients receive on average 3 to 6 sessions of physiotherapy per week, though intensity varies depending on the patients' physical endurance and formalized agreements employed by the rehabilitation units. 27 Additional treatment aspects during geriatric rehabilitation concern general medical care, fall prevention, osteoporosis, nutrition, and fear or depression.…”
Section: Treatment and Assessmentsmentioning
confidence: 99%